European postgraduate training in geriatric medicine: data of a systematic international survey - Singler, Katrin; Holm, Ellen Astrid; Jackson, Thomas; Robertson, Gillian; Mueller-Eggenberger, Eva; Roller, Regina Elisabeth (Aging Clinical and Experimental Research, 2015)
High-quality education and training standards in geriatric medicine are important to develop the profession of geriatric medicine. The objective of the study was to give a structured update on postgraduate specialty training in geriatric medicine throughout Europe to assess the need for further developments in postgraduate education.The study was performed as a cross-sectional structured quantitative online survey with qualitative comments. The survey content covered organization, content and educational aspects of specialty training in geriatric medicine in European countries. After piloting, the questionnaire was sent to experts in geriatric medicine with a special interest in postgraduate training who are members of one of the following organizations; European Union of Medical Specialists (UEMS), European Academy for the Medicine of Aging (EAMA), and European Union Geriatric Medicine Society (EUGMS).Respondents to the survey represented 31 European countries. Geriatric medicine is recognized as an independent postgraduate specialty in 61.3 % (19/31) and as a subspecialty in 29.0 % (9/31) of the countries. In 5 of the 31 countries geriatric medicine is not recognized at all. Nearly all countries offering postgraduate training in geriatric medicine have written, competence-based curricula covering different learning domains. 20/31 countries (64.5 %) have some kind of specialist assessment.The survey tries to give an actual condensed picture of postgraduate specialty training in geriatric medicine across Europe. Results show a consistent improvement in the recognition of geriatric medicine as independent specialty over the last decade. Continuous development of specialty training in geriatric medicine is required to medical address the public health needs of an aging population. Competence-based educational models including adequate forms of assessment should be targeted throughout Europe. To emphasize the importance of postgraduate geriatric training, it should be a mission to harmonize training standards across Europe.
EVALuna2:10578